From adoption to assisted reproduction : frameworks, practices and issues surrounding the question of origins and its narratives - Martial, Agnès; Côté, Isabel; Lavoie, Kévin (Enfances, Familles, Générations, 2021)
Research Framework: In a context characterized by new possibilities for parenthood within societies where family structures are becoming increasingly diverse, the issue of knowing one's origins is currently provoking intense political, social and scientific debates. These debates are emblematic of a more general movement that reflects a growing interest in the question of origins within contemporary patterns of family configuration, whether created by adoption or assisted reproduction . The concept of origins is thus a particularly relevant window shedding light on current social and political issues surrounding the future of adoption, the conditions for assisted reproduction through donation, the legislative framework of surrogacy and the application of biogenetic knowledge, as well as an opportunity to analyze contemporary reconfigurations of kinship and family links. Objectives: To identify the primary issues underlying the discourse on personal origins by outlining the context from which it emerged, and by bringing together the various disciplinary approaches to define its parameters. Methodology: This article is based on the various authors' contributions in this issue, as well as on theoretical and empirical studies that show how the concept of origins is used by those involved in adoption and assisted reproduction . The comparative perspective is chosen for this article. Results: The focus on origins reveals a profound evolution linked to the growing dissociation of procreation from kinship, which appear to be leading to the emergence of "new" relationships and actors. The rapid advancement of reproductive technologies is broadening the circumstances, already present in adoption, in which people have children but do not become parents in the legal sense, remaining "at the edges" of kinship. Conclusions: The concept of origins provides a particularly rich field for examining current representations and interpretations of the individuals associated with it (birth "parents" in adoption, egg and sperm donors, women who have carried a child for others), the narratives that shape them, and the place they occupy (or their absence) in the accounts of those who are adopted or are born through surrogacy. Contribution: This article brings a theoretical and heuristic approach to the concept of origins and demonstrates its relevance for examining the multiple relational realities created by current family arrangements. The articles in this issue all contribute to this examination by reflecting in complementary ways on the question of parentage.